Cultural Tapestry: The Role of Popular Culture in Shaping Identities and Modernity in Pakistan - Maimoona Rasool (Al-Qanṭara, 2024)
Popular culture shapes the identities, ideas and actions of civilizations, acting as a dynamic tapestry woven into the fabric of everyday existence. Pakistan is a country of rich in historical and cultural diversity. The popular culture provides a unique lens to explore the interaction between tradition and modernity, as well as the tension between local and global influences. The paper explores how popular culture mediates the complex dynamics between deeply rooted traditions and the pressures of modernization in Pakistan. It also looks at the effect of global cultural flows on local practices and values. The research guiding questions this are: How does popular culture influence the identities and behaviors of individuals in Pakistan? What role does it play in negotiating the tension between practice and modernity? How do global cultural influences reshape local practices in Pakistan? Marwan M. Kraidy has highlighted the significance of popular culture in shaping societal norms and values particularly in contexts marked by cultural hybridity and social transformation. The work highlights the need to understand of how popular culture interacts with other social forces in shaping collective identities. The study is based in the Cultural Hegemony theory of Gramsci Antonio, which theorizes that popular culture play a crucial role in maintaining or challenging power structures in society. The framework is used to analyze how popular culture in Pakistan either reinforces or resists dominant cultural narratives. The paper objects to reveal the ways in which popular culture in Pakistan serves as a landscape of both traditionalism and struggle that offers insights into the broader processes of cultural negotiation and identity formation in a rapidly changing society.